WHATSAPP GROUP-BASED ENGLISH SCHOOL IN COVID-19 PANDEMIC - Suardi, Suardi; Pratiwi, Widya Rizky (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
This study describes the members’ motivation and learning process in WhatsApp Group-based English School (WG-ES) as a unique platform to organize self-productivity during COVID-19. This study used the qualitative method. Fifty-one members participated. The instruments used were Google forms, observations, and documents. The data were analyzed using adopted six approaches by Cresswell. The results indicated that the participants joined WG-ES based on their desires and awareness. Their motivations for joining WG-ES were divided into English-based and non-English-based motivations. Most participants were motivated to improve their English skills, specifically communication skills. The other motivations were the expectation to expand networking, get experience, and find an opportunity to study abroad. In WG-ES, the learning programs were divided into two main activities, daily chitchat and focused learning. WG-ES had rules, study schedules, and flexible curriculums. Therefore, the participants seemed more comfortable studying English through WG-ES. Abstrak: Penelitian ini menggambarkan motivasi dan proses belajar anggota di Sekolah Bahasa Inggris berbasis Grup WhatsApp sebagai platform yang produktif selama COVID-19. Penelitian ini menggunakan metode kualitatif. Lima puluh satu anggota berpartisipasi dalam penelitian ini. Instrumen yang digunakan adalah Google-form, observasi, dan dokumen. Data dianalisis menggunakan enam pendekatan yang diadopsi oleh Cresswell. Hasil penelitian menunjukkan bahwa peserta mengikuti Grup WhatsApp berdasarkan keinginan dan kesadaran mereka. Motivasi untuk bergabung Grup WhatsApp terbagi menjadi motivasi berbasis bahasa Inggris dan non-bahasa Inggris. Sebagian besar peserta termotivasi untuk meningkatkan kemampuan bahasa Inggris, khususnya keterampilan komunikasi. Motivasi lainnya adalah harapan untuk memperluas jaringan, mendapatkan pengalaman, dan menemukan kesempatan untuk belajar di luar negeri. Dalam Grup WhatsApp ini, program pembelajaran dibagi menjadi dua kegiatan utama, yaitu obrolan harian dan pembelajaran terfokus. Sekolah Bahasa Inggris berbasis Grup WhatsApp ini memiliki aturan, jadwal belajar, dan kurikulum yang fleksibel. Oleh karena itu, para peserta lebih nyaman belajar bahasa Inggris melalui Sekolah Bahasa Inggris berbasis Grup WhatsApp.